Proceedings of the Winter Simulation Conference
DOI: 10.1109/wsc.2002.1166447
|View full text |Cite
|
Sign up to set email alerts
|

Panel session: opportunities for simulation in supply chain management

Abstract: It has become a matter of survival that many companies improve their supply chain efficiency. This presents an opportunity for simulation. However, there are many challenges that must be overcome for simulation to be a contributor to play an effective role. Four contributors discuss the opportunities that they see for simulation to play a meaningful role in the area of supply chain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 7 publications
0
28
0
2
Order By: Relevance
“…Simulation provides firms with a perspective on supply chain dynamics and its efficacy [8]. Simulating a supply chain implies a behaviour that integrates logistic and production networks which represent complex inter-and intra-organisational facilities characteristics, physical entities and resources [9][10][11]. In supply chain simulation, some studies about bullwhip avoidance techniques are found in Cannella et al [12][13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simulation provides firms with a perspective on supply chain dynamics and its efficacy [8]. Simulating a supply chain implies a behaviour that integrates logistic and production networks which represent complex inter-and intra-organisational facilities characteristics, physical entities and resources [9][10][11]. In supply chain simulation, some studies about bullwhip avoidance techniques are found in Cannella et al [12][13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They include to a large extent the general optimization tasks which are to be performed by SCM (Archibald et al 1999(Archibald et al , p. 1207. The target variables of simulation studies concentrate mainly on a reduction of cost, the optimization of material and information flows, the reduction of processing and lead times, or a consequent process-related orientation of the company (Banks et al 2002). A recent study analyzes over 80 articles which describe an application of Supply Chain Simulation either in an industrial pilot project, commercially available software, or a simulation test within a logistics chain (Terzi and Cavalieri 2004).…”
Section: Discrete Event Simulation For Supporting Industrial Process mentioning
confidence: 99%
“…Discrete event simulation is an important method in supply chain management (Kleijnen, 2003). A survey of supply chain simulation applications, including commonly used commercial packages, is found in Banks et al (2002).…”
Section: Research Approachmentioning
confidence: 99%